Impact of Seasonal Variations on Economic Grainage Traits of Muga Silkworm (Antheraea assamensis) in Garo Hills, India - , Vikram Kumar; , Abhishek Singh; , M. Majumdar; , Narendra Kumar; , N. K. Bhatia (Archives of Current Research International, 2025)
Muga silkworm (Antheraea assamensis Helfer) is one of the most important silkworms in the sericulture industry and muga silk having high economic demand in the market. Muga silkworm belongs to the order Lepidoptera and family Saturniidae. Being polyphagous and multivoltine, it produces 5 to 6 generation per year and categorised into pre-seed, seed and commercial crop. The pre-seed and seed crops of Muga usually fall in adverse climatic seasons of extreme summer and winter and the productivity sometimes slashes down to 10- 20%.. This study aimed to evaluate the impact of seasonal variations on the grainage traits of Muga silkworms in Garo Hills. The findings revealed that the Baisakhi and Late Bhodia seasons recorded a significantly high coupling, DFL:DFL, Fecundity and Hatching percentage as compared with Aherua and Aghenua season. High temperature, high rainfall, heavy disease and pest infestation during Aherua season and longer duration, low temperature, high fungal infestation and dry climate during Aghenua season reduced the overall yield of muga silkworm.